Pyruvate Kinase M2 Is Required for the Expression of the Immune Checkpoint PD-L1 in Immune Cells and Tumors - Palsson-McDermott, Eva M.; Dyck, Lydia; Zasłona, Zbigniew; Menon, Deepthi; McGettrick, Anne F.; Mills, Kingston H. G.; O’Neill, Luke A. (Frontiers in Immunology, 2017)
Blocking interaction of the immune checkpoint receptor PD-1 with its ligand PD-L1 is associated with good clinical outcomes in a broad variety of malignancies. High levels of PD-L1 promote tumour growth by restraining CD8+ T-cell responses against tumors. Limiting PD-L1 expression and function is therefore critical for allowing the development of anti-tumour immune responses and effective tumour clearance. PKM2 is also a key player in regulating cancer as well as immune responses. PKM2 catalyzes the final rate-limiting step of glycolysis. Furthermore PKM2 as a dimer translocates to the nucleus, where it stimulates Hif-1α transactivation domain function and recruitment of p300 to the Hif-1α response elements (HRE) of Hif-1α target genes. Here, we provide the first evidence of a role for PKM2 in regulating the expression of PD-L1 on macrophages, dendritic cells (DCs), T cells and tumour cells. LPS-induced expression of PD-L1 in primary macrophages was inhibited by the PKM2 targeting compound TEPP-46. Furthermore, RNA silencing of PKM2 inhibited LPS-induced PD-L1 expression. This regulation occurs through direct binding of PKM2 and Hif-1α to HRE sites on the PD-L1 promoter. Moreover, TEPP-46 inhibited expression of PD-L1 on macrophages, DCs and T cells as well as tumour cells in a mouse CT26 cancer model. These findings broaden our understanding of how PKM2 may contribute to tumour progression, and may explain the upregulation of PD-L1 in the tumour microenvironment.